Malcolm at midnight - Beck, W. H., 1970- (Houghton Mifflin Books for Children, 2012)
Malcolm, a smaller than average rat, loves life at McKenna School and the secret society of classroom pets that keep children out of trouble, but when Aggy the iguana disappears Malcolm must use all of his ratty persistence to prove his innocence and save her.